2011
DOI: 10.1597/09-219
|View full text |Cite
|
Sign up to set email alerts
|

β-TCP versus Autologous Bone for Repair of Alveolar Clefts in a Goat Model

Abstract: The synthetic bone substitute β-TCP was shown to result in bone healing similar to that of iliac crest bone. The surgical, orthodontic, and histologic results now warrant the testing of β-TCP in the human cleft situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…The alveolar region has its own particular characteristics, predominantly consisting of cancellous bone that is thinner and has higher porosity than the calvarial bone. 34 Thus, it is an ideal site to test less brittle materials: first, because there is no need to protect the underlying neurovascular bundle, and second, because a softer material presents a higher porosity that can ultimately simulate the cancellous bone of this region and also facilitate teeth eruption and mobilization during orthodontia. Therefore, the mechanical strength in this region is of less importance when compared to the calvarial region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The alveolar region has its own particular characteristics, predominantly consisting of cancellous bone that is thinner and has higher porosity than the calvarial bone. 34 Thus, it is an ideal site to test less brittle materials: first, because there is no need to protect the underlying neurovascular bundle, and second, because a softer material presents a higher porosity that can ultimately simulate the cancellous bone of this region and also facilitate teeth eruption and mobilization during orthodontia. Therefore, the mechanical strength in this region is of less importance when compared to the calvarial region.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mechanical strength in this region is of less importance when compared to the calvarial region. De Ruiter et al 34 repaired alveolar defects in a goat model using β-TCP. De Ruiter et al 34 emphasized the importance of orthodontic tooth movement while repairing an alveolar defect with these biomaterials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was then established that TCP graft made better bone regeneration than the autograft did. 3 According to an experiment on mice conducted by Ru N et al, TCP graft had higher osteoconductivity and better biomechanic property than cancellous bone graft or without graft. 4 Another research on humans has shown that there was remarkable bone volume addition (73% ± 6% of its initial volume) during 6 months after bone grafting with TCP.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that β -TCP alone implantation is not sufficient to fill the defect with regenerated bone in the craniofacial region. Some experimental studies have confirmed the osteoconductive properties of β -TCP, which were comparable to autologous bone grafts [15, 17, 70]. However, other groups have emphasized versatility by combining β -TCP with autologous bone fragments [16, 7779], growth factors [45, 46, 8084], simvastatin [71], or stem cells [18, 85, 86] in both experimental and clinical studies.…”
Section: Discussionmentioning
confidence: 99%